Knowledge, attitude and practices on biomedical waste and its management among health care workers at a tertiary care hospital in Koppal, Karnataka, India - Mane, Vijaykumar; Nimbannavar, Smita M.; B. Y., Yuvaraj (International Journal Of Community Medicine And Public Health, 2016)
Background: Biomedical waste carries a higher potential for infection and injury than any other type of waste. Inadequate and inappropriate handling of such waste may have serious public health consequences and a significant impact on the environment. Health care workers are the key workers in the management of biomedical waste and their inadequate knowledge, unfavorable attitude and poor practices are dangerous for their own health and those in the society. The objective of the present study was to assess the knowledge, attitude and practices on biomedical waste and its management among health care workers in the study setting. Methods: A cross sectional study was conducted among 162 health care workers at a tertiary care hospital in Koppal district of Karnataka state. Data was collected using a pretested and semi structured questionnaire after taking an informed consent and analysed using WHO Epi info software. Results: The present study found out that the health care workers had satisfactory level of knowledge, favorable attitude and better practices towards biomedical waste management. However, their practices were not in proportion to the level of their knowledge and attitude. Conclusions: Regular training, continuous monitoring and behaviour change communication are recommended to improve their biomedical waste handling practices.